A Project feasibility study on coconut flour as wheat flour substitute - Baysic, Enrico; Deligente, Estelita; Guillermo, Marie Antoinette; Pisang, Maribeth; Salazar, Ma. Teresa; Tan, Remedios (Diliman, Quezon City College of Engineering, 1984)
The series of peso devaluations against the dollar and the devaluations that are yet to come has made importation very expensive. The present economic crisis has forced the Filipinos to work and strive harder in order to make both ends meet. It is very timely, therefore, to look into the development of imported products from indigenous locally-available raw materials. Our country is rich in natural resources and makes use of them in order to ease up the economic crises we are experiencing. Bread and other bakery products are a part of our day-to-day meals and snacks. But these are no longer cheap commodities. You see, bread and the pother bakery products come from wheat flour. Wheat is not commercially grown in the Philippines and is thus, imported at present from wheat producing countries such as the United States, Japan, Holland, etc. Because of the Central Bank restrictions on opening letters of credit, wheat importation is being limited and the volume has been reduced from 850,000 metric tons annually to only 775,000 metric tons. This move has caused shortages of flour and black-marketing such that it forced the government thru the NFA to take over the distribution and allocation of hard and soft flour from the flour millers. The take-over since December 1983 succeeded in flushing out colorum bakeries as only registered bakers and end-users were given flour allocations. Deputy Administrator Pablo V. Pablo of the National Food Authority (NFA) said that increasing our importation by 100,000 metric tons per year would end our flour shortage problem. However, as this is unlikely to occur, a wheat flour substitute has to be found to augment the flour supply. Many flour substitutes have been developed on a laboratory scale such as corn flour, kalabasa flour and banana flour, and on a much larger scale such as cassava flour. This feasibility study investigates the potential of yet another flour substitutes, the coconut flour. The only flour substitute being produced in quantities is cassava flour. A Presidential Decree has been issued ordering the use of cassava flour at a 10:90 ratio with wheat flour. Due to poor implementation, the substitution did not materialize and the manufacturers of cassava flour have turned to producing more cassava starch from which glucose can be made. Bakers, for their part, are also reluctant to substitute even at a small percentage because of the minimal price differential between substituting and not substituting. Mixing wheat flour and cassava flour also has an effect on the yield factor although no noticeable change in taste is observed. Therefore, if a flour substitute can be developed that is available at a very low cost and can thus mean huge savings for the baker/user, and then maybe bakers would think twice before opting not to substitute. There have been a number of studies made on the production of coconut flour and about twelve (12) methods have been developed. The methods or procedures can be subdivided into the wet and dry processes. The resulting flour made from the wet process is not stable so only a discussion of the dry processes was indulged into this study. Of the five methods of making flour using the dry process, coconut flour from copra was selected as the best technique based on specified criteria. Production of coconut flour from copra starts with the deshelling and paring of the nuts and subsequently, their drying in a chain dryer for twenty four (24) hours. Oil is expressed from the copra thru the use of expellers. High-oil flour is more prone to deterioration if not kept very dry so that the oil content from the expelled meal has to be further reduced. This is done by solvent extraction. The resulting meal is then grinned and packed as coconut flour. The coconut oil is collected in a tank and sold to UNICOM at the world market as crude coconut oil. From the parings, oil can also be extracted. The paring oil and the coconut residual cake can both be sold to the world market...
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Coconut flour; Cooking (Coconut flour).; Participatory monitoring and evaluation (Project management)